Bacteroides fragilis와 대장균의 혼합 감염에 의한 복강 조직의 Proinflammatory Cytokine 유전자 발현 조절 - 김정목; 김영전; 박훤겸; 조양자; Kim, Jung-Mogg; Kim, Young-Jeon; Park, Hwon-Kyum; Cho, Yang-Ja (The journal of the Korean Society for Microbiology, 2000)
Bacteroides fragilis and Escherichia coli, normal colonic inhabitants, are the most frequently isolated bacteria in infected tissues, particularly in intraabdominal abscesses. This study was designed to determine whether enteric bacteria may alter the B. fragilis-induced expression of pro inflammatory cytokines in mouse peritoneal tissue (MPT). After C57BL/6 mice were inoculated with abscess-forming mixture containing B. fragilis in the presence or absence of E. coli, RNA was extracted from MPT. Expression of interleukin (IL)-$1α$ and tumor necrosis factor $(TNF)α$ mRNA was assessed using RT-PCR and standard RNA. Each cytokine protein was also measured by ELISA. The co-inoculation of E. coli into mouse peritoneal cavity advanced the onset of abscess development by B. fragilis infection. When mouse was co-infected with E. coli and B. fragilis intraperitoneally, there was a synergistic increase in the expression of IL-$1α$ and $TNFα$ mRNA in MPT and this was paralleled by increased cytokine protein secretion. Mixed inoculation of heat-killed E. coli and B. fragilis did not cause a synergistic increase in those cytokine mRNA expression. These results suggest that enteric bacteria may significantly affect proinflammatory cytokine signal produced by host peritoneal cavity in response to B. fragilis infection.